2016
DOI: 10.1053/j.semdp.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Castleman disease: Where are we now?

Abstract: Multicentric Castleman disease (MCD) encompasses a spectrum of conditions that give rise to overlapping clinicopathological manifestations. The fundamental pathogenetic mechanism involves dysregulated cytokine activity, which causes systemic inflammatory symptoms as well as lymphadenopathy. The histological changes in lymph nodes resemble in part the findings originally described in the unicentric forms Castleman disease, both hyaline vascular and plasma cell variants. In MCD caused by Kaposi sarcoma-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 126 publications
2
105
1
2
Order By: Relevance
“…9 We sometimes observed the "lollipop sign" of prominent blood vessels radially penetrating GCs and "budding" or "twinning" of follicles, which involves $2 GCs located within a single follicle. 5,9 Historically, many features of this group would be described as consistent with the "hyaline vascular" (HV) histopathologic subtype of MCD. However, many hematopathologists consider HV to only occur in UCD based on the classic descriptions by Benjamin Castleman, and a few HV-UCD features, such as FDC dysplasia and sclerotic vessels, are not often observed in MCD.…”
Section: Major Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…9 We sometimes observed the "lollipop sign" of prominent blood vessels radially penetrating GCs and "budding" or "twinning" of follicles, which involves $2 GCs located within a single follicle. 5,9 Historically, many features of this group would be described as consistent with the "hyaline vascular" (HV) histopathologic subtype of MCD. However, many hematopathologists consider HV to only occur in UCD based on the classic descriptions by Benjamin Castleman, and a few HV-UCD features, such as FDC dysplasia and sclerotic vessels, are not often observed in MCD.…”
Section: Major Criteriamentioning
confidence: 99%
“…5 Other virally-associated lymphoproliferations or uncontrolled infections that should be considered include Epstein-Barr virus (EBV)-associated lymphoproliferative disorders, such as infectious mononucleosis or chronic active EBV infection, but low levels of EBV are not necessarily exclusionary.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…4 Furthermore, recent studies have revealed that patients with multi-centric CD exhibit elevated serum concentrations of IgG4 and interleukin-6, and abundant infiltration of IgG4-positive cells in the affected organs. 5 MuSK antibodies are primarily associated with IgG4, in contrast to acetylcholine receptor antibodies, which are primarily associated with IgG1 or IgG3.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is a rarely encountered, poorly understood, lymphoproliferative disorder that really comprises a broad spectrum of clinicopathologic entities and has widely variable therapeutic outcomes. 3 Unicentric and multicentric variants have been described. Unicentric CD (UCD) is confined to one lymph node region and is usually treated by lymph node excision; inflammatory symptoms are mild and typically abate with lymph node removal.…”
mentioning
confidence: 99%